Electrospun rubber fibre mats with electrochemically controllable pore sizes1. Issue 20 (28th May 2015) - Kerr-Phillips, Thomas E.; Woehling, Vincent; Agniel, Remi; Nguyen, Giao T. M.; Vidal, Frederic; Kilmartin, Paul; Plesse, Cédric; Travas-Sejdic, Jadranka
<x xml:space="preserve">Abstract</x> Electroactive, elastomeric, microfiber mats that show controllable pore size variation upon electrochemical stimulation are produced from semi-interpenetrating polymer networks (s-IPNs).